Safety and immunogenicity of the oral, inactivated, enterotoxigenic Escherichia coli vaccine ETVAX in Bangladeshi children and infants: a double-blind, randomised, placebo-controlled phase 1/2 trial. Issue 2 (February 2020) - Qadri, Firdausi; Akhtar, Marjahan; Bhuiyan, Taufiqur R; Chowdhury, Mohiul I; Ahmed, Tasnuva; Rafique, Tanzeem A; Khan, Arifuzzaman; Rahman, Sadia I A; Khanam, Farhana; Lundgren, Anna; Wiklund, Gudrun; Kaim, Joanna; et al.
Summary: Background: Enterotoxigenic Escherichia coli causes diarrhoea, leading to substantial mortality and morbidity in children, but no specific vaccine exists. This trial tested an oral, inactivated, enterotoxigenic E coli vaccine (ETVAX), which has been previously shown to be safe and highly immuongenic in Swedish and Bangladeshi adults. We tested the safety and immunogenicity of ETVAX, consisting of four E coli strains overexpressing the most prevalent colonisation factors (CFA/I, CS3, CS5, and CS6) and a toxoid (LCTBA) administered with or without a double-mutant heat-labile enterotoxin (dmLT) as an adjuvant, in Bangladeshi children. Methods: We did a randomised, double-blind, placebo-controlled, dose-escalation, age-descending, phase 1/2 trial in Dhaka, Bangladesh. Healthy children in one of three age groups (24–59 months, 12–23 months, and 6–11 months) were eligible. Children were randomly assigned with block randomisation to receive either ETVAX, with or without dmLT, or placebo. ETVAX (half [5·5 × 10 10 cells], quarter [2·5 × 10 10 cells], or eighth [1·25 × 10 10 cells] adult dose), with or without dmLT adjuvant (2·5 μg, 5·0 μg, or 10·0 μg), or placebo were administered orally in two doses 2 weeks apart. Investigators and participants were masked to treatment allocation. The primary endpoint was safety and tolerability, assessed in all children who received at least one dose of vaccine. Antibody responses to vaccine antigens, defined as at least a two-times increase in antibody levels between baseline and post-immunisation, were assessed as secondary endpoints. This trial is registered with ClinicalTrials.gov, NCT02531802 . Findings: Between Dec 7, 2015, and Jan 10, 2017, we screened 1500 children across the three age groups, of whom 430 were enrolled and randomly assigned to the different treatment groups (130 aged 24–59 months, 100 aged 12–23 months, and 200 aged 6–11 months). All participants received at least one dose of vaccine. No solicited adverse events occurred that were greater than moderate in severity, and most were mild. The most common solicited event was vomiting (ten [8%] of 130 patients aged 24–59 months, 13 [13%] of 100 aged 12–23 months, and 29 [15%] of 200 aged 6–11 months; mostly of mild severity), which appeared related to dose and age. The addition of dmLT did not modify the safety profile. Three serious adverse events occurred but they were not considered related to the study drug. Mucosal IgA antibody responses in lymphocyte secretions were detected against all primary vaccine antigens (CFA/I, CS3, CS5, CS6, and the LCTBA toxoid) in most participants in the two older age groups, whereas such responses to four of the five antigens were less frequent and of lower magnitude in infants aged 6–11 months than in older children. Faecal secretory IgA immune responses were recorded against all vaccine antigens in infants aged 6–11 months. 78 (56%) of 139 infants aged 6–11 months who were vaccinated developed mucosal responses against at least three of the vaccine antigens versus 14 (29%) of 49 of the infants given placebo. Addition of the adjuvant dmLT enhanced the magnitude, breadth, and kinetics (based on number of responders after the first dose of vaccine) of immune responses in infants. Interpretation: The encouraging safety and immunogenicity of ETVAX and benefit of dmLT adjuvant in young children support its further assessment for protective efficacy in children in enterotoxigenic E coli -endemic areas. Funding: PATH (Bill & Melinda Gates Foundation and the UK's Department for International Development), the Swedish Research Council, and The Swedish Foundation for Strategic Research.